AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN SONG OF BRUNO MARS ENTITLED “GRENADE” - Fajrin, Maudy Yaser; Parmawati, Aseptiana (IKIP Siliwangi, 2021)
Individuals use language as a means of communication everywhere and at all times. In today's world, figurative language is often encountered in everyday life, such as in song lyrics. Figurative language is a way of describing something without saying it directly. This research aims to investigate the figurative languages found in the lyrics of the song